Real-time web-cast system by multihop WebRTC communications. (2018) - Ito, Daiki; Niibori, Michitoshi; Kamada, Masaru
A software system is developed for casting the screen images and voices from a host PC to the client web browsers on many other PCs in real time. This system is intended to be used in the classrooms. Students have only to bring their own PCs and connect to the teacher's host PC by a web browser via a wireless network to see and listen to the teaching materials presented on the host PC. Then the client web-browsers are organised in the shape of a binary tree along which the video and audio data are relayed in the multihop fashion by the Web Real-Time Communication (WebRTC) protocol. This structure of binary multihop relay is adopted in order not to burden the host PC with communications load. A test has shown that voice and the motion pictures in a rather small size of 320 × 240 pixels on a teacher's PC have been presented at the rate of 5 frames per second without any conceivable delays on the web browsers running on 38 client devices for students under a local WiFi network. To host more client devices, we have to lower the frame rate as slow as the slide show of still pictures.